The impact of COVID-19 infections on pregnancy outcomes in women - Ke Xu; Wen Sun; Shuangshuang Yang; Tianqi Liu; Ning Hou (BMC, 2024)
Abstract Background Given that viral infections can increase the risk of adverse pregnancy outcomes, such as spontaneous miscarriage, preterm premature rupture of membranes, and preterm birth, the effects of COVID-19, a novel emerging coronavirus disease rapidly spreading globally, on pregnancy outcomes have garnered significant attention. Methods We conducted a review of studies related to pregnant women infected with SARS-CoV-2 over the past five years (December 2019 to April 2023), utilizing search engines such as PubMed, Web of Science, and the China National Knowledge Infrastructure (CNKI). This study was registered with PROSPERO with ID: CRD42024540849. Results A total of 218 articles were screened, with 15 studies meeting the inclusion criteria for this research, including 12 cohort studies, one cross-sectional study, one case-control study, and one case series. Six studies found that the preterm birth rate was higher in the infected group compared to the control group; five studies showed that the cesarean section rate was higher in the infected group; three studies found that the APGAR scores of newborns were higher in the control group than in the infected group; three studies indicated that the mortality rate of newborns in the infected group was higher than that in the control group. Conclusions Our retrospective review suggests that compared to pregnant women not infected with SARS-CoV-2, those diagnosed with COVID-19 are more likely to experience adverse outcomes such as preterm birth, cesarean delivery, and low birth weight in newborns.